Lo Que Usted Calla, El Cuerpo Lo Grita” Lógicas Acerca De La Vivencia De Enfermedades Del Sistema Reproductor Femenino Y Su Relación Con Situaciones De Conflictos No Apalabrados En 5 Mujeres De La Ciudad De Bogotá (2019)
The following research was done with the purpose of learning from the personal experiences of women who suffer from diseases stemming from the female reproductive system and their relation to undisclosed emotional conflicts. For this, a study of a qualitative nature was undertaken, utilizing a descriptive design approach of the aforementioned conflicts and the life experiences associated with said diseases. Five women suffering from these female reproductive system diseases, and supported via psychoanalytical theory by means of content analysis; in addition to psychoanalytical and psychosomatic theoretical indicators including the differentiation between the conversion symptom and the psychosomatic phenomenon pertaining to the undisclosed conflict situation, were interviewed to delve deeper into the theoretical aspects that psychosomatics provide.